Aanbidding en prediking in missionale gemeentes – homileties- liturgiese beskouinge van missionêre gemeentebediening - Smit, Guillaume H. (HTS teologiese studies, 2010)
In the context of changes in society and the resulting paradigm shifts in theological thinking, this article explores the development of a missional ministry praxis for church services in the reformed theological tradition. This is done through a basic overview on recent theological developments in missional ecclesiology, homiletics and liturgy and a case study of a congregation who made the shift to missional ministry praxis by renewing its church services. Opportunities for further research is identified and the conclusion is made that churches who made the theological paradigm shift to missional ministry must inherently change the character and planning of their church services to reflect and further develop this change.